2021
DOI: 10.3390/molecules26092429
|View full text |Cite
|
Sign up to set email alerts
|

Self-Crosslinked Ellipsoidal Poly(Tannic Acid) Particles for Bio-Medical Applications

Abstract: Self-crosslinking of Tannic acid (TA) was accomplished to obtain poly(tannic acid) (p(TA)) particles in single step, surfactant free media using sodium periodate (NaIO4) as an oxidizing agent. Almost monodisperse p(TA) particles with 981 ± 76 nm sizes and −22 ± 4 mV zeta potential value with ellipsoidal shape was obtained. Only slight degradation of p(TA) particles with 6.8 ± 0.2% was observed at pH 7.4 in PBS up to 15 days because of the irreversible covalent formation between TA units, suggesting that hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…This may be due to the three-dimensional structure of the cryogels in comparison to the linear CS polymer, as well as to the existence of DVS groups that may have some kind of affinity to bind with Fe(II) ions. The similar behavior was also observed for tannic acid and poly(tannic acid) particles; the particle form of tannic acid afforded significant increase in Fe(II) cheating capability [ 35 ]. Moreover, it was also reported that a flavonoid, rutin molecule showed no binding ability for the Fe(II) ion, whereas the micro/nanogels form of rutin had considerable Fe(II) binding ability [ 5 ].…”
Section: Resultssupporting
confidence: 58%
“…This may be due to the three-dimensional structure of the cryogels in comparison to the linear CS polymer, as well as to the existence of DVS groups that may have some kind of affinity to bind with Fe(II) ions. The similar behavior was also observed for tannic acid and poly(tannic acid) particles; the particle form of tannic acid afforded significant increase in Fe(II) cheating capability [ 35 ]. Moreover, it was also reported that a flavonoid, rutin molecule showed no binding ability for the Fe(II) ion, whereas the micro/nanogels form of rutin had considerable Fe(II) binding ability [ 5 ].…”
Section: Resultssupporting
confidence: 58%
“…In this context, it is known that some polyphenols have an affinity for binding Fe 2+ ions. Tannic acid (TA) chelates with Fe 2+ ions [ 97 ]. Depending on the concentration, other phenolic compounds such as catechin molecules also chelate with Fe 2+ ions in the aqueous environments [ 98 ].…”
Section: Novel Phyto-therapeutic Approaches In Admentioning
confidence: 99%
“…Polyethylene terephthalate (PET) is the most widespread single use plastic but, its natural properties are only marginally resistant to ultraviolet light penetration which can lead to the initiation of the autoxidation process . Many natural compounds (e.g., tannic acid, catechin, cyanidin, caffeic acid, quercetin, ellagic acid, xanthan and 8-hydroxygenistein) have been demonstrated as effective autoxidation reducing molecules with an order of effectiveness of some of them as catechin > cyanidin ≈ caffeic acid > quercetin > ellagic acid …”
Section: Introductionmentioning
confidence: 99%